A case report of severe pulmonary legionellosis caused by Legionella bozemanae - Xu, Peixing; Wang, Fang; Ren, Hongyu; Ni, Wentao; Zhao, Na; Li, Ran; Chen, Yanwen; Gao, Zhancheng; Qin, Tian (Frontiers in Bacteriology, 2024)
We report a case of Legionnaires’ disease caused by Legionella bozemanae, which is the first time that L. bozemanae has been isolated from a bronchoalveolar lavage fluid sample from an immunocompromised patient in China. The findings highlight the susceptibility of immunocompromised patients to infections caused by the rare but highly pathogenic L. bozemanae.